Ekstrak air daun ceplikan (Ruellia tuberosa L.) serta pengaruhnya terhadap kadar glukosa darah dan gambaran histologis pankreas tikus putih (Rattus norvegicus) diabetes mellitus - Taufan Hendra Tandri; Wiryatun Lestariana; Fatma Zuhrotun Nisa (Jurnal Gizi Klinik Indonesia, 2009)
Background: Effective control of blood glucose and activities of antioxidant are key factors that prevent diabetes mellitus (DM) and its complications. There are lots of herbal plants that have those both effects. Ceplikan leaves (Ruellia tuberosa L.) is a traditional medicine which is empirically used to lower blood glucose level. Instead of antioxidant compound, there is assumed other compound in ceplikan leaves that has side effect to pancreatic beta cells.Objective: To identify the effect of ceplikan leaves extract to blood glucose level and pancreas histology description in white diabetic rats (Rattus norvegicus).Method: Thirty subjects of Wistar strain male white rats of 2-3 months old and of 150-200 grams weight were made diabetic with aloxan and randomly divided into 5 groups. Group I consisted of diabetic rats with aquadest, group II with glibenclamide, and Group III-V were given extract of ceplikan leaves in different concentrations that were 1.6 mg, 3.2 mg, and 6.4mg, respectively. Treatment was given orally per day within 30 days. Level of blood glucose was measured in the day of 0, 3, 4, and 30. Statistical analysis used repeated measures and t-test.Result: The supply of ceplikan leaves extract could reduce level of blood glucose of diabetic rats, although the decrease was insignificant. Average diameter of wider Langerhans island occurred to the group of diabetic rats that were given extract of ceplikan leaves dosage 6.4 mg. There was no significant difference (p > 0.05) in changes of blood glucose level before and after experiment in diabetic rats. Pancreas histological description of rats showed that there was improvement as indicated by greater quantity of Langerhans Island and wider diameter of Langerhans Island.Conclusion: Ceplikan leaves was safe and efficacious, so that self-medication of DM using ceplikan leaves could be sustained through formal approach.